Oral Wild-Type Salmonella Typhi Challenge Induces Activation of Circulating Monocytes and Dendritic Cells in Individuals Who Develop Typhoid Disease - Toapanta, Franklin R.; Bernal, Paula J.; Fresnay, Stephanie; Darton, Thomas C.; Jones, Claire; Waddington, Claire S.; Blohmke, Christoph J.; Dougan, Gordon; Angus, Brian; Levine, Myron M.; Pollard, Andrew J.; Sztein, Marcelo B. (PLoS neglected tropical diseases, 2015)
A new human oral challenge model with wild-type Salmonella Typhi (S. Typhi) was recently developed. In this model, ingestion of 104 CFU of Salmonella resulted in 65% of subjects developing typhoid fever (referred here as typhoid diagnosis -TD-) 5-10 days post-challenge. TD criteria included meeting clinical (oral temperature ≥38°C for ≥12 h) and/or microbiological (S. Typhi bacteremia) endpoints. One of the first lines of defense against pathogens are the cells of the innate immune system (e.g., monocytes, dendritic cells -DCs-). Various changes in circulating monocytes and DCs have been described in the murine S. Typhimurium model; however, whether similar changes are present in humans remains to be explored. To address these questions, a subset of volunteers (5 TD and 3 who did not develop typhoid despite oral challenge -NoTD-) were evaluated for changes in circulating monocytes and DCs. Expression of CD38 and CD40 were upregulated in monocytes and DCs in TD volunteers during the disease days (TD-0h to TD-96h). Moreover, integrin α4β7, a gut homing molecule, was upregulated on monocytes but not DCs. CD21 upregulation was only identified in DCs. These changes were not observed among NoTD volunteers despite the same oral challenge. Moreover, monocytes and DCs from NoTD volunteers showed increased binding to S. Typhi one day after challenge. These monocytes showed phosphorylation of p38MAPK, NFkB and Erk1/2 upon stimulation with S. Typhi-LPS-QDot micelles. In contrast, monocytes from TD volunteers showed only a moderate increase in S. Typhi binding 48 h and 96 h post-TD, and only Erk1/2 phosphorylation. This is the first study to describe different activation and migration profiles, as well as differential signaling patterns, in monocytes and DCs which relate directly to the clinical outcome following oral challenge with wild type S. Typhi.